Epidemiology and molecular characterisation of SPFMV, SPVG and SPLCV infecting sweetpotato in South Africa - Mulabisana, Mapula Julia (My University, 2018)
Root crops such as sweetpotato [(Ipomoea batatas (L.) Lam.] are highly regarded as alternative food sources to address food insecurities in South Africa and other African countries. Sweetpotato viruses, commonly occurring in mixed infections of viruses of different taxonomic groups are a threat to production of sweetpotato. Potyviruses, belonging to the Potyviridae family are virus species Sweet potato feathery mottle virus, Sweet potato virus G, Sweet potato virus C and Sweet potato virus 2 and these have been reported to occur in South Africa. Crinivirus species Sweet potato chlorotic stunt virus, belonging to the Closteroviridae family was also reported. Monopartite, single stranded DNA begomoviruses are also a threat to sweetpotato production globally. All these viruses were detected in South Africa in previous studies. Symptoms associated with potviruses include mild chlorotic spots and in severe cases, plants may develop some chlorotic spots with purple pigmentations, mild vein banding and in some cases, plants may be symptomless. Symptoms caused by crinivirus SPCSV alone are relatively mild on sweetpotato and plants may become mildly stunted. Plants infected with begomoviruses may exhibit mild upward curling of the leaves, however, it is reported that plants may also appear symptomless in the field. Begomovirus species Sweet potato leaf curl Sao Paulo virus and Sweet potato mosaic virus were reported to occur in the Limpopo Province of South Africa in 2012. This led to field surveys being conducted to determine the prevalence of potyviruses and begomoviruses in the three provinces of South Africa, namely, Limpopo, Gauteng and Mpumalanga. Furthermore, to characterize Sweet potato feathery mottle virus (SPFMV), Sweet potato virus C (SPVC), Sweet potato virus G (SPVG) and Sweet potato leaf curl virus (SPLCV) by means of partial genome cloning and sequencing, and full genome sequencing using next generation sequencing (NGS). Surveys were conducted over two seasons and a total sample number of 272 (2012/13) and 332 (2013/14) of sweetpotato samples were grafted onto the indicator plant Ipomoea setosa [(I. setosa (Kerr.)] Kerr to observe for viii virus related symptoms. Virus disease incidences were low and these were 18% (Limpopo Province), 19% (Mpumalanga Province) and 23% (Gauteng Province) in season 1, 4% (Limpopo Province), 21% (Gauteng Province) and 22% (Mpumalanga Province), however, this varied in areas within the three provinces surveyed. Infestations of adult aphids and whiteflies as virus vectors were low (1-5 insects score equivalent to low infestation). Inspite of low virus disease incidences in the field, and low infestations of aphids and whiteflies, viruses were identified in both asymptomatic and symptomatic samples grafted onto I. setosa using nitrocellulose enzyme linked immunosorbent assay (NCM-ELISA), double antibody ELISA, reverse transcription polymerase chain reaction (RT-PCR) and PCR to verify the identity of viruses. The incidence of SPFMV, either as single or co-infection with SPVC was 52% and 16% in season 1 and 2, respectively. SPVG (1.5% and 35%), SPCSV (2% and 16%), Sweet potato mild mottle virus (SPMMV) (3% and 5%), SPV2 (3% and 8%) and Sweet potato mild speckling virus (SPMSV) (2% and 2.4%) were also detected, in season 1 and 2, respectively. Other viruses detected include Sweet potato chlorotic fleck virus (SPCFV) and Sweet potato latent virus (SwPLV) in low (0.6 to 1%) incidences in both seasons. Viruses were also detected in single infections with the most common single infection being that of SPFMV. Mixed infections of SPFMV and SPVG were common and those of SPFMV/SPVG and SPCSV were also detected. There was a need to characterize and to determine the genetic variability of potyviruses SPFMV, SPVC and SPVG, and to investigate the possible occurrences of begomoviruses in the three provinces since such information was lacking. Genetic characterization was accomplished by partial genome sequencing for potyviruses (SPFMV, SPVC and SPVG) and full-length genome sequencing for begomovirus isolates. A total of 5 (SPVC), 4 (SPFMV), 6 (SPVG) and 9 (begomoviruses) isolates were sequenced and analyzed. Phylogeny, pairwise ix comparison and analysis of the coat protein (CP) encoding amino acid (aa) sequences revealed that the russet crack (RC) strain of SPFMV in this study shared 97% to 99% nucleotide (nt) identity with isolates reported in other parts of the world and that it was the only strain of SPFMV detected in the three provinces surveyed. SPVC isolates in this study were also confirmed to share the nt identity of between 86% to 94% with isolates reported in South Africa (Kwazulu Natal Province, Western Cape Province) and other parts of the world. SPVG was also confirmed to occur in the three provinces surveyed and minor sequence variability at nt level were observed between isolates in this study and those reported in Kwazulu Natal Province. However, analysis of the CP encoding aa sequences confirmed that all analysed isolates are the same strain of SPVG. Rolling circle amplification (RCA) and full-length genome sequencing with next generation sequencing (NGS) detected begomoviruses. Sweet potato leaf curl SaoPaulo virus (SPLCSPV) and Sweet potato mosaic virus (SPMV) were confirmed to occur in the Gauteng Province. SPLCSPV isolate Tanz: ELLP_ZA (Limpopo Province) and SPLCSPV isolate Tanz: NMP-ZA (Mpumalanga Province) were related to SPLCSPV isolate TZ-SNG7:12 of Tanzania, with which they shared the nt identity of 94% and 95%, respectively. TMBLP-ZA was identified as a novel isolate of SPLCV and we propose that it is classified as SPLCV isolate South Africa (ZA): TMBLP-ZA. The effects of begomoviruses SPLCSPV/SPLCV and SPMV on the yield of sweetpotato varieties is not widely studied and this led to the study expanding to determine the effects of these viruses as mixed infections of two begomoviruses and potyviruses. Two field trials were planted in January 2014 and 2015 with eight locally bred sweetpotato varieties (Bophelo, Impilo, Ndou, Monate, Mvuvhelo, Blesbok, Bosbok and Ribbok), three from the United States of America (USA) (W-119, Hernandez and Resisto) and one (199062.1) from the International Potato Centre (CIP, Lima, Peru). Single and co-infections of potyviruses and begomoviruses in sources of virus combinations were confirmed by NCM-ELISA, RT-PCR, PCR and NGS. Virus treatments (T) were as follows: T1= co-infections of SPFMV (RC strain) + SPVG + SPVC + begomoviruses (SPLCSV + SPMV), T2 = co-infections of SPFMV (RC strain) + begomoviruses, T3=single infection of SPFMV (RC strain), T4= co-infection of SPLCSV + SPMV. The total and marketable yield of all 12 varieties was significantly reduced by treatments T1 and T2, and the yield was severely decreased in trial 2 with all the treatments. Treatments T3 and 4 also reduced the total and marketable yield, however, varieties differed in their responses to these treatments. The total yield reduced with T3 were between 27% and 78% in trial 1, and varieties such as Bophelo, Hernandez, Impilo and Ribbok had yield reductions of less than 50%, when compared to the other eight varieties. However, the yields were severly reduced in trial 2 (61% to 99%). Total average yield were also reduced with begomovirus co-infections (T4) and yield losses were between 32% and 84% in trial 1, and varieties such as Bophelo, Bosbok, Mvuvhelo, Ndou and Resisto had yield reductions of less than 50%, when compared to the other seven varieties. Production of low and poor quality yield in sensitive sweetpotato varieties in South Africa was confirmed to be due to begomoviruses as mixed infection of SPLCSPV/SPLCV and SPMV, in mixed infections with potyviruses. The findings in this study of seven distinct virus species, is significant as it is associated with high yield losses. The quality of sweetpotato is therefore compromised, which ultimately affect the livelihoods of those who depend on the crop for household consumption and as a source of income. Stringent disease management strategies to prevent virus spread ais urgently needed and farmers to be taught how prevent the spread. Furthermore, the government need to implement robust quarantine regulations to prevent new virus strains from entering the country.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy in the School of Molecular and Cell Biology. Johannesburg, September 2018
Keywords: Sweetpotato whitefly--Biological control--South Africa; Virus diseases of plants; Insect-plant relationships